Lixisenatide Improves Glycemic Control in Asian Type 2 Diabetic Patients Inadequately Controlled With Oral Antidiabetic Drugs: An Individual Patient Data Meta-Analysis. Issue 4 (December 2016) - Shu, Hua; Gu, Li-na; Men, Li-chuang; Lu, Ju-ming
Abstract Introduction Lixisenatide is a novel GLP-1 receptor agonist for the treatment of type 2 diabetes mellitus (T2DM). Its efficacy and safety have been assessed in a series of phase 3 studies included in the GetGoal program. In these studies, lixisenatide was found to be superior to placebo in glycemic control. The aim of this meta-analysis was to assess the safety and efficacy of lixisenatide as an adjunct therapy in Asian patients with T2DM in adequately controlled with oral antidiabetic drugs (OADs). Methods We performed a meta-analysis from five lixisenatide phase 3 studies. In each of these multiethnic studies, patients with T2DM inadequately controlled (glycated hemoglobin, HbA1c ≥7%) with established OADs were randomized to lixisenatide or placebo for 24 weeks, with a balanced distribution of Asian patients in these two arms (503 and 338 patients in the intent-to-treat population, respectively). Results Lixisenatide was superior to placebo in reducing HbA1c (weighted, total mean difference −0.57%;P = 0.002). More patients treated with lixisenatide versus placebo achieved HbA1c targets of ≤7% (49.1% vs. 28.4%, P = 0.003). Lixisenatide was superior to placebo in lowering 2-h postprandial glucose (PPG) (weighted, total mean difference −5.50 mmol/l, P = 0.0005). More patients treated with lixisenatide versus placebo achieved 2-h PPG targets of ≤7.8 mmol/l (39.2% vs. 2.2%, P < 0.0001). More patients treated with lixisenatide versus placebo achieved both an HbA1c target of ≤7% and a 2-h PPG target of ≤10 mmol/l (34.8% vs. 2.69%, P < 0.00001). The body weight of the lixisenatide group tended to decrease. Lixisenatide was generally well tolerated. Conclusion Lixisenatide as an adjunct therapy can significantly improve the glycemic control of Asian patients with type 2 DM who do not meet targets for glycemic control with an established OAD regimen. Funding Sanofi (China) Investment Co., Ltd., Shanghai, China.